Magnetorheological fluid as well as preparation method and application thereof

Through the method of modifying magnetic particles on the surface of polysiloxane, the problems of insufficient stability of the magnetorheological fluid and limited magnetic field response capabilities are solved, and low zero-field viscosity, high shear yield stress and good settlement resistance are achieved.

CN119763973APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411755550.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing magnetorheological fluids have problems such as insufficient stability, high zero-field viscosity, fast sedimentation rate and limited magnetic field response capabilities.

Method used

The surface modified magnetic particles of polysiloxane are modified by hydrolysis and dehydration condensation reactions to form a magnetorheological liquid with excellent dispersion and anti-settlement properties.

Benefits of technology

It significantly improves the long-term stability of magnetorheological fluid, reduces zero-field viscosity, improves shear yield stress, and enhances the response ability under the magnetic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763973A_ABST
    Figure CN119763973A_ABST
Patent Text Reader

Abstract

The invention relates to a magnetorheological fluid and a preparation method and application thereof.The magnetorheological fluid contains polysiloxane surface modified magnetic particles, polysiloxane is obtained by polycondensation of at least one silane with the general formula being X-Si-(OR) 3, X is selected from substituted or unsubstituted alkyl with the carbon atom number being 10-16, and R2 is selected from substituted or unsubstituted alkyl with the carbon atom number being 10-16. R is selected from substituted or unsubstituted alkyl with the carbon atom number of 1-3, and the weight-average molecular weight of polysiloxane is 500-20000. The magnetorheological fluid disclosed by the invention has relatively low zero-field viscosity, relatively high shear yield stress and long-term stability, is particularly suitable for a vehicle damping system, has the capabilities of quick response and damping adjustment, and is beneficial to improving the performance of the damping system and prolonging the service life of the damping system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a magnetorheological fluid and a preparation method and application thereof. Background Art

[0002] Magnetorheological fluid (MRF) is a smart material formed by uniform dispersion of magnetic particles in a non-magnetic carrier fluid. It exhibits the free-flowing characteristics of a liquid when no magnetic field is applied, and can be transformed into a high-viscosity material with a solid-like phase within milliseconds when a magnetic field is applied. This adjustable rheological property makes magnetorheological fluid have broad prospects in applications such as semi-active vibration reduction and impact control.

[0003] At present, magnetorheological fluid has been widely used in automobile suspension systems, and the damping characteristics of shock absorbers are adjusted by controlling the magnetic field, thereby improving the comfort and handling performance of the vehicle. However, the existing magnetorheological fluid technology still has many shortcomings. For example, magnetic particles are easy to settle and aggregate, resulting in insufficient long-term stability of magnetorheological fluid. Although increasing the viscosity of the slurry will improve the problem of too fast sedimentation rate, the higher zero-field viscosity will increase the zero-field damping force, limiting the response ability of the magnetorheological fluid under the magnetic field.

[0004] Therefore, how to effectively improve the stability of magnetorheological fluid while taking into account low zero-field viscosity, low sedimentation rate and high shear yield stress under a specific magnetic field is a key issue that needs to be urgently solved in the current research on magnetorheological fluid preparation. Summary of the invention

[0005] The purpose of the present disclosure is to provide a magnetorheological fluid with improved anti-settling property, lower zero-field viscosity and higher shear yield stress, and a preparation method and application thereof.

[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a magnetorheological fluid, wherein the magnetorheological fluid contains magnetic particles with surface modified by polysiloxane, wherein the polysiloxane is obtained by condensation polymerization of at least one silane with the general formula X-Si-(OR)3, wherein X is selected from a substituted or unsubstituted alkyl group with a carbon number of 10 to 16, and R is selected from a substituted or unsubstituted alkyl group with a carbon number of 1 to 3, and the weight average molecular weight of the polysiloxane is 500 to 20,000.

[0007] Optionally, in the silane, the substituents in X and R are each independently selected from a methoxy group, an ethoxy group, a halogen group, a hydroxyl group, an amino group, a thiol group, a carboxyl group, an amide group, and a nitrile group.

[0008] Optionally, in the silane, X is selected from a straight-chain alkyl group having 10 to 16 carbon atoms, and R is selected from a methyl group, an ethyl group, and a n-propyl group.

[0009] Optionally, the polysiloxane includes a first polysiloxane and a second polysiloxane, the first polysiloxane is obtained by condensation of a first silane with a general formula of X1-Si-(OR)3, and the second polysiloxane is obtained by condensation of a second silane with a general formula of X2-Si-(OR)3, X1 and X2 are each independently selected from a substituted or unsubstituted alkyl group with a carbon number of 10 to 16, and the carbon number of X1 is less than the carbon number of X2.

[0010] Optionally, in the first silane, X1 is selected from a straight-chain alkyl group having 10 to 12 carbon atoms, and in the second silane, X2 is selected from a straight-chain alkyl group having 14 to 16 carbon atoms.

[0011] Optionally, the magnetorheological fluid further includes a base fluid and an additive. Based on the total weight of the magnetorheological fluid, the content of the magnetic particles is 70-85% by weight, the content of the base fluid is 12-22% by weight, and the content of the additive is 2-9% by weight.

[0012] Optionally, the base fluid includes one or more of mineral oil, synthetic hydrocarbon oil, ester oil, silicone oil, natural oil and fluorine oil.

[0013] Optionally, the additives include a thixotropic agent, an antiwear agent and an antioxidant. Based on the total weight of the magnetorheological fluid, the content of the thixotropic agent is 1-4 weight %, the content of the antiwear agent is 0.5-2 weight %, and the content of the antioxidant is 0.5-2 weight %.

[0014] Optionally, the thixotropic agent includes one or more of nano-silicon dioxide, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax and polyvinyl chloride.

[0015] Optionally, the anti-wear agent includes one or more of graphite, molybdenum disulfide, organic molybdenum compounds, sulfur-phosphorus compounds, chlorophosphorus compounds, chlorosulfur compounds, organic phosphides and organic metal salts.

[0016] Optionally, the antioxidant includes one or more of an organic phosphorus compound, an organic molybdenum compound, a zinc dialkyl dithiophosphate, a zinc alkyl thiocarbamate, a phenolic compound and a complex antioxidant.

[0017] Optionally, the magnetorheological fluid has a 30-day sedimentation rate of less than 20%, a zero-field viscosity of less than 500 mPa·s, and a shear yield stress of more than 70 kPa at a magnetic field strength of 0.8 T.

[0018] In a second aspect of the present disclosure, a method for preparing the magnetorheological fluid according to the first aspect of the present disclosure is provided, the method comprising: obtaining an acidic solution containing alcohol and water; The mixture of magnetic particles, at least one silane of the general formula X-Si-(OR)3 and the acidic solution is subjected to hydrolysis and dehydration condensation reaction to obtain a reacted material; wherein X is selected from a substituted or unsubstituted alkyl group having 10 to 16 carbon atoms, R is selected from a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, the weight average molecular weight of the polysiloxane is 500 to 20,000, and the weight ratio of the magnetic particles to the silane is 100:(3 to 10); Washing and drying the reacted material to obtain polysiloxane surface-modified magnetic particles; The magnetorheological fluid is prepared by using the polysiloxane surface-modified magnetic particles.

[0019] Optionally, the acidic solution further contains glacial acetic acid; and / or the pH value of the acidic solution is 3-5. Optionally, the weight ratio of the water to the alcohol is 1:(0.2-2); and / or, The weight ratio of the magnetic particles to the acidic solution is 1:(0.5-3).

[0020] Optionally, the hydrolysis conditions include: temperature of 20-30° C., stirring speed of 500-1000 rpm, and time of 1-5 h; and / or, The dehydration condensation conditions include: temperature of 50-90° C., stirring speed of 500-1000 rpm, and time of 0.1-5 h; and / or, The drying conditions include: a temperature of 70-90° C. and a time of 8-20 hours.

[0021] Optionally, the method further comprises: ball-milling a mixture of the polysiloxane surface-modified magnetic particles, the base fluid and the additive to obtain the magnetorheological fluid.

[0022] Optionally, the ball milling conditions include: a rotation speed of 300-500 rpm and a time of 4-12 h.

[0023] A third aspect of the present disclosure provides an application of the magnetorheological fluid described in the first aspect of the present disclosure in a vehicle shock absorbing device.

[0024] Through the above technical scheme, the magnetorheological fluid disclosed in the present invention contains special polysiloxane surface-modified magnetic particles, which exhibit excellent dispersibility and anti-sedimentation properties in the carrier liquid, significantly improving the long-term stability of the magnetorheological fluid, so that the magnetorheological fluid disclosed in the present invention has both low zero-field viscosity and high shear yield stress, and is particularly suitable for vehicle shock absorption systems. It has the ability to respond quickly and adjust damping, which helps to improve the performance and service life of the shock absorption system.

[0025] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 is a schematic diagram of the microstructure of magnetic particles with polysiloxane surface modification in a magnetorheological fluid according to a specific embodiment; Figure 2 The present invention is a schematic diagram of the preparation process of polysiloxane surface-modified magnetic particles according to a specific embodiment. DETAILED DESCRIPTION

[0027] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0028] According to a first aspect of the present disclosure, a magnetorheological fluid is provided, the magnetorheological fluid containing magnetic particles with a surface modified by polysiloxane, the polysiloxane being obtained by polycondensation of at least one silane of the general formula X-Si-(OR)3, wherein X is selected from a substituted or unsubstituted alkyl group having 10 to 16 carbon atoms, R is selected from a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, and the weight average molecular weight of the polysiloxane is 500 to 20,000.

[0029] In the magnetorheological fluid disclosed in the present invention, the magnetic particles are formed into spherical shapes, and the polysiloxane obtained by polycondensation of silane containing long-chain alkyl groups is coated on the surface of the magnetic particles. Figure 1 The steric hindrance of polysiloxane can overcome the van der Waals force between magnetic particles and prevent the magnetic particles from agglomerating with each other, thereby improving the dispersion effect in the magnetic particle carrier and reducing the slurry viscosity. At the same time, by coating with polysiloxane, the polar groups (such as hydroxyl groups) on the surface of the magnetic particles are modified into non-polar long-chain alkyl groups, thereby changing their surface properties from hydrophilic to hydrophobic, and having better compatibility with the oil-phase base liquid. In addition, it is also beneficial to reduce the particle density, narrow the density difference between the magnetic particles and the carrier liquid, further improve the anti-settling effect of the magnetorheological fluid, and significantly improve the long-term stability of the magnetorheological fluid, ensuring that the magnetorheological fluid still has a low sedimentation rate and a high shear yield stress when the zero-field viscosity is small.

[0030] In the present disclosure, the term "substituted or unsubstituted" means that the functional group recorded after the term may or may not have a substituent, and the number of substitutions may be one or more. The number of carbon atoms of the substituted or unsubstituted functional group refers to the number of all carbon atoms. The alkyl group may include a straight-chain alkyl group and a branched-chain alkyl group. In one embodiment, the substituents in X and R are each independently selected from a methoxy group (-OCH3), an ethoxy group (-OC2H5), a halogen group (-Cl, -Br or -I), a hydroxyl group (-OH), an amino group (-NH2), a thiol group (-SH), a carboxyl group (-COOH), an amide group (-CONH2), and a nitrile group (-CN).

[0031] The polysiloxane has a suitable weight average molecular weight to achieve the desired surface modification effect. When the weight average molecular weight of the polysiloxane is too large, the long molecular segments are easily entangled with each other, resulting in poor fluidity; when the weight average molecular weight of the polysiloxane is too small, it may not be able to effectively cover the surface of the magnetic particles, and the modification effect is not significant.

[0032] In the silane X-Si-(OR)3, the number of carbon atoms of the X group and the R group has a key influence on the dispersibility and anti-sedimentation properties of the magnetic particles. When the number of carbon atoms of the X group is less than 10, the steric hindrance of the formed polysiloxane is small, the dispersibility is insufficient, and an obvious self-condensation reaction will occur to form polycondensates between the particles, causing the magnetic particles to agglomerate; and when the number of carbon atoms of the X group is greater than 16, the whip sheath structure at the grafted end with the magnetic particles is too long and easily entangled with each other, resulting in an increase in the viscosity of the magnetorheological fluid, and an excessively thick coating layer will also reduce the magnetic saturation strength of the magnetic particles, limiting the shear yield stress of the magnetorheological fluid under a magnetic field. The R group is first hydrolyzed during the modification process. When the number of carbon atoms of the R group is greater than 3, the hydrolysis efficiency is low, which is not conducive to achieving the desired modification and grafting effect.

[0033] In a preferred embodiment, in the silane X-Si-(OR)3, X is selected from a straight-chain alkyl group with a carbon number of 10 to 16; R is selected from a methyl group, an ethyl group, and a n-propyl group, and is more preferably a methyl group. In this case, the polysiloxane coating layer formed is beneficial to maximally improve the dispersibility and anti-sedimentation properties of the magnetic particles, so that the magnetorheological fluid has excellent comprehensive properties.

[0034] Specifically, the silane may include dodecyltrimethoxysilane ( )、Hexadecyltrimethoxysilane( )、Dodecyltriethoxysilane() 、Dodecyltri(chloromethoxy)silane( )、Hexadecyltri(mercaptomethoxy)silane( When silanes with different carbon number alkyl groups are used for modification, various polysiloxanes with different structures can be obtained accordingly.

[0035] In a specific embodiment, the surface modification of magnetic particles by combining silanes of different structures is beneficial to further improve the anti-sedimentation effect of magnetic particles and enhance the comprehensive performance of magnetorheological fluid. Preferably, the polysiloxane includes a first polysiloxane and a second polysiloxane, the first polysiloxane is obtained by polycondensation of a first silane of the general formula X1-Si-(OR)3, the second polysiloxane is obtained by polycondensation of a second silane of the general formula X2-Si-(OR)3, X1 and X2 are independently selected from substituted or unsubstituted alkyl groups with 10 to 16 carbon atoms, and the number of carbon atoms of X1 is less than the number of carbon atoms of X2, R is selected from substituted or unsubstituted alkyl groups with 1 to 3 carbon atoms, and the optional range of substituents in X1, X2 and R is consistent with that described above; at this time, due to the different lengths of the carbon chains of the polysiloxanes on the surface of the magnetic particles, a "mixed whip sheath" structure can be formed, and a stable cross-linked network coating structure is constructed on the surface of the magnetic particles, which significantly improves the long-term stability of the magnetorheological fluid. For example, in the first silane, X1 can be selected from a linear alkyl group having 10 to 12 carbon atoms, and in the second silane, X2 can be selected from a linear alkyl group having 14 to 16 carbon atoms.

[0036] According to the present disclosure, the polysiloxane surface-modified magnetic particles refer to magnetic particles obtained by surface-modifying magnetic particles using the silane described above.

[0037] In a specific embodiment, the preparation step of the polysiloxane surface-modified magnetic particles may include the following steps S1 to S3: S1, obtaining an acidic solution containing alcohol and water; S2, subjecting the mixture of the magnetic particles, at least one of the silanes mentioned above and the acidic solution to hydrolysis and dehydration condensation reaction to obtain a reacted material; S3, washing and drying the reacted material to obtain the polysiloxane surface-modified magnetic particles.

[0038] In step S1, the pH value of the acidic solution may be 3 to 5. In order to achieve the desired pH value and avoid corrosion to the magnetic particles, the acidic solution may further contain glacial acetic acid. The weight ratio of the water to the alcohol may be 1:(0.2 to 2), and the alcohol may be one or more of ethanol, isopropanol, ethylene glycol and methanol.

[0039] In step S2, the magnetic particles may be spherical carbonyl iron powder, and the average particle size thereof may be 1 to 10 μm. In order to obtain a polysiloxane with a desired weight average molecular weight, the weight ratio of the magnetic particles to the silane may be 100:(3 to 10), preferably 100:(4 to 7). In the embodiment in which the polysiloxane described above includes the first polysiloxane and the second polysiloxane, the weight ratio of the first silane to the second silane may be adjusted within a certain range, specifically 1:(0.5 to 2.0). The amount of the acidic solution may be adjusted within a wide range, for example, the weight ratio of the magnetic particles to the acidic solution may be 1:(0.5 to 3).

[0040] The hydrolysis and / or dehydration condensation can be carried out under ultrasonic conditions. Specifically, the hydrolysis conditions may include: a temperature of 20-30°C, a stirring speed of 500-1000 rpm, and a time of 1-5 hours; the dehydration condensation conditions may include: a temperature of 50-90°C, a stirring speed of 500-1000 rpm, and a time of 0.1-5 hours. Figure 2 During the hydrolysis process, the alkoxy group (-OR) connected to Si in the silane forms a silanol group (Si-OH), and then the silanol groups undergo dehydration condensation and react with the hydroxyl groups (-OH) on the surface of the magnetic particles to form hydrogen bonds, ultimately obtaining a polysiloxane with siloxane as the basic repeating unit and connected to the surface of the magnetic particles by a strong covalent bond, namely a silicon-oxygen bond (-O-Si-).

[0041] In step S3, the reacted material can be washed to neutrality by the washing. The drying can be performed under vacuum conditions, and specifically, the drying conditions may include: a temperature of 70-90° C. and a time of 8-20 hours.

[0042] According to the present disclosure, the magnetorheological fluid may further include a base fluid and an additive, and the content of each component in the magnetorheological fluid may be adjusted within a certain range. In a specific embodiment, based on the total weight of the magnetorheological fluid, the content of the magnetic particles may be 70-85% by weight, the content of the base fluid may be 12-22% by weight, and the content of the additive may be 2-9% by weight. Preferably, based on the total weight of the magnetorheological fluid, the content of the magnetic particles is 76-80% by weight, the content of the base fluid is 17-20% by weight, and the content of the additive is 3-7% by weight. The above ratio is conducive to achieving the best comprehensive performance of the magnetorheological fluid.

[0043] The base fluid may include one or more of synthetic mineral oil, synthetic hydrocarbon oil (such as poly-α-olefin), ester oil (such as diester oil and polyester oil), silicone oil, natural oil and fluorine oil, preferably poly-α-olefin. The viscosity index (VI) of the base fluid may be ≥100 to achieve excellent comprehensive performance of the magnetorheological fluid.

[0044] The specific type of the additive can be selected according to actual needs. In a specific embodiment, the additive can include a thixotropic agent, an anti-wear agent and an antioxidant. Further, based on the total weight of the magnetorheological fluid, the content of the thixotropic agent can be 1-4 weight %, the content of the anti-wear agent can be 0.5-2 weight %, and the content of the antioxidant can be 0.5-2 weight %.

[0045] The thixotropic agent, anti-wear agent and antioxidant can be common in the art. In a specific embodiment, the thixotropic agent can include one or more of nano-silicon dioxide, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax and polyvinyl chloride, and the above thixotropic agent can be fully activated in the carrier liquid to form a reversible three-dimensional hydrogen bond network supporting magnetic particles; the anti-wear agent can include solid lubricants and liquid lubricants, preferably solid lubricants, specifically graphite, molybdenum disulfide, organic molybdenum compounds, sulfur-phosphorus compounds, chlorine-phosphorus compounds, chlorine-sulfur compounds, organic phosphides and organic metal salts. One or more of the antioxidants can include organic phosphorus compounds, organic molybdenum compounds, zinc dialkyl dithiophosphates, alkyl thiocarbamate zinc, phenolic compounds (such as dibutylhydroxybenzene compounds, hydroxystilbene compounds) and complex antioxidants (such as sulfur antioxidants, silicon antioxidants, etc.).

[0046] The magnetorheological fluid disclosed in the present invention has low zero-field viscosity, high shear yield stress and long-term stability. Specifically, the 30-day sedimentation rate of the magnetorheological fluid can be less than 20%, preferably less than 15%; the zero-field viscosity can be less than 500mPa·s, preferably less than 400mPa·s; the shear yield stress under a magnetic field strength of 0.8T can be more than 70kPa, preferably more than 75kPa. The magnetorheological fluid is particularly suitable for vehicle shock absorption systems, has the ability to respond quickly and adjust damping, and helps to improve the performance and service life of the shock absorption system.

[0047] In a second aspect of the present disclosure, a method for preparing the magnetorheological fluid according to the first aspect of the present disclosure is provided, the method comprising the following steps S1 to S4: S1, obtaining an acidic solution containing alcohol and water; S2, subjecting the mixture of the magnetic particles, at least one silane and the acidic solution to hydrolysis and dehydration condensation reaction to obtain a reacted material; S3, washing and drying the reacted material to obtain polysiloxane surface-modified magnetic particles.

[0048] S4. Using the polysiloxane surface-modified magnetic particles to prepare magnetorheological fluid.

[0049] The specific implementation of steps S1 to S3 is described above.

[0050] In one embodiment, step S4 may include: ball-milling a mixture of the polysiloxane surface-modified magnetic particles, a base liquid and additives to obtain the magnetorheological fluid. The specific types of the base liquid and the additives are as described in the first aspect of the present disclosure. Furthermore, the base liquid and the additives may be evenly mixed to obtain a carrier liquid, and then the carrier liquid and the mixture of the polysiloxane surface-modified magnetic particles may be ball-milled to obtain a magnetorheological fluid. The conditions for mixing the base liquid and the additives may include: a stirring speed of 800 to 1000 rpm and a time of 30 to 180 min.

[0051] The ball milling can be performed using an appropriate amount of ball milling media (such as stainless steel grinding balls, etc.). Specifically, the weight ratio of the mixed material to the ball milling media can be 1: (1-5). The ball milling conditions can include: a rotation speed of 300-500 rpm and a time of 4-12 hours.

[0052] The third aspect of the present disclosure provides an application of the magnetorheological fluid described in the first aspect of the present disclosure in a vehicle shock absorption system. For example, the magnetorheological fluid can be used in a semi-active suspension structure of a vehicle, and its fast response and precise adjustment characteristics enable the vehicle to adjust the suspension performance in real time according to different driving conditions and road conditions, thereby achieving higher comfort, controllability and safety.

[0053] The present disclosure is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the present disclosure.

[0054] The raw materials and reagents used in the examples and comparative examples are all commercially available products.

[0055] Example 1 The composition of the magnetorheological fluid of this embodiment is as follows: 78% by weight of magnetic particles, 17% by weight of base fluid, 3.0% by weight of thixotropic agent, 1.0% by weight of anti-wear agent, and 1.0% by weight of antioxidant. The specific preparation steps are as follows: (1) 78.0 g of carbonyl iron powder (average particle size 4-6 μm) was dried at 70 °C in a vacuum of 0.1 MPa for 12 h to remove physically adsorbed water on the surface.

[0056] (2) Add an appropriate amount of glacial acetic acid to deionized water, then mix in an appropriate amount of ethanol in a water-to-alcohol weight ratio of 1:1, adjust the amount of glacial acetic acid, stir evenly, and obtain an acidic solution with a pH of 4.0.

[0057] (3) 3.90 g (5%) of decyltrimethoxysilane (C 10 H 21 -Si-(OCH3)3) is added to 200g of the acidic solution of step (2), and at the same time, dry carbonyl iron powder is added, and ultrasonic stirring treatment is carried out under the following conditions: room temperature 25°C, ultrasonic frequency 40KHz, stirring rate 800rpm, and hydrolysis time 1.5h; then, the stirring rate and ultrasonic frequency are kept unchanged, the temperature is increased to 80°C, and maintained for 0.5h for dehydration condensation to obtain a suspension.

[0058] (4) The suspension obtained in step (3) was repeatedly washed with anhydrous ethanol until it was neutral, filtered and dried in a vacuum drying oven at 80°C for 10 hours, with a vacuum degree of 0.1 MPa. After drying, the obtained block solid was ground into powder and passed through a 100-mesh sieve to obtain magnetic particles with polydecylsiloxane (weight average molecular weight of 5250) surface modified. The contact angle of the magnetic particles with deionized water was 124.93° using the dynamic contact angle method, and the polar solution condensed into small balls on the surface of the magnetic particles, indicating that the magnetic particles have a very good hydrophobic effect. (5) Add 3.0 g of organic bentonite to 17.0 g of poly-α-olefin (viscosity index is 120), add 1.0 g of molybdenum disulfide and 1.0 g of zinc dialkyl dithiophosphate, and stir at 1000 rpm for 30 min to obtain a mixed carrier liquid. Add the magnetic particles obtained in step (4) to the mixed carrier liquid, place in a ball mill, add stainless steel bead milling balls at a weight ratio of 1:2 between the mixed material and the milling balls, and mill at 300 rpm for 5 h, including 30 min of forward rotation and 30 min of reverse rotation, and repeat for 5 times. After grinding, separate the ball liquid to obtain a uniform black magnetorheological fluid.

[0059] Example 2 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of dodecyltrimethoxysilane (C 12 H 25 -Si-(OCH3)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polydodecylsiloxane (weight average molecular weight of 7400).

[0060] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0061] Example 3 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of tetradecyltrimethoxysilane (C 14 H 29 -Si-(OCH3)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polytetradecylsiloxane (weight average molecular weight of 9100).

[0062] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0063] Example 4 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of hexadecyltrimethoxysilane (C 16 H 33 -Si-(OCH3)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polyhexadecylsiloxane (weight average molecular weight of 10750).

[0064] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0065] Example 5 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of hexadecyltriethoxysilane (C 16 H 33 -Si-(OC2H5)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polyhexadecylsiloxane (weight average molecular weight of 10750).

[0066] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0067] Example 6 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 1.95 g of decyltrimethoxysilane and 1.95 g of tetradecyltrimethoxysilane were used for surface modification to obtain magnetic particles with surface modified polydecylsiloxane and polytetradecylsiloxane (weight average molecular weight of 7400).

[0068] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0069] Example 7 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 1.95 g of dodecyltrimethoxysilane and 1.95 g of hexadecyltrimethoxysilane were used for surface modification to obtain magnetic particles with surface modified by a polymer of polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 9150).

[0070] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0071] Example 8 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 1.17 g of dodecyltrimethoxysilane and 1.17 g of hexadecyltrimethoxysilane were used for surface modification to obtain magnetic particles with surface modified by a polymer of polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 9600).

[0072] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0073] Example 9 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 3.90 g of dodecyltrimethoxysilane and 3.90 g of hexadecyltrimethoxysilane were used for surface modification to obtain magnetic particles with surface modified polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 10750).

[0074] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0075] Example 10 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 3.90 g of hexadecyl tris(mercaptomethoxy)silane (C 16 H 33 -Si-(OCH2SH)3) was surface-modified to obtain magnetic particles with surface modified polyhexadecylsiloxane (weight-average molecular weight of 10900).

[0076] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0077] Embodiment 11 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (2), hydrochloric acid was used instead of glacial acetic acid to obtain an acidic solution with a pH of 4.0.

[0078] The weight percentage of each component of the magnetorheological fluid of this embodiment is the same as that of embodiment 1.

[0079] Example 12 A magnetorheological fluid was prepared according to the method of Example 1, except that the amount of materials used in step (5) was different. The composition of the magnetorheological fluid of this example is as follows: 79% by weight of magnetic particles, 17% by weight of base fluid, 2.0% by weight of thixotropic agent, 1.0% by weight of anti-wear agent, and 1.0% by weight of antioxidant.

[0080] Example 13 A magnetorheological fluid was prepared according to the method of Example 1, except that the amount of materials used in step (5) was different. The composition of the magnetorheological fluid of this example is as follows: 71% by weight of magnetic particles, 21% by weight of base fluid, 4.0% by weight of thixotropic agent, 2.0% by weight of anti-wear agent, and 2.0% by weight of antioxidant.

[0081] Embodiment 14 A magnetorheological fluid was prepared according to the method of Example 1, except that the amount of materials used in step (5) was different. The composition of the magnetorheological fluid of this example is as follows: 84% by weight of magnetic particles, 14% by weight of base fluid, 1.0% by weight of thixotropic agent, 0.5% by weight of anti-wear agent, and 0.5% by weight of antioxidant.

[0082] Comparative Example 1 A magnetorheological fluid was prepared according to the method of Example 1, except that unmodified carbonyl iron powder was directly used as magnetic particles.

[0083] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0084] Comparative Example 2 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of octyltrimethoxysilane (C8H 17 -Si-(OCH3)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polyoctylsiloxane (weight average molecular weight of 4100).

[0085] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0086] Comparative Example 3 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), the same amount of octadecyltrimethoxysilane (C 18 H 37 -Si-(OCH3)3) was used to replace decyltrimethoxysilane for surface modification to obtain magnetic particles with surface modified with polyoctadecylsiloxane (weight average molecular weight of 13500).

[0087] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0088] Comparative Example 4 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 0.39 g of dodecyltrimethoxysilane and 0.39 g of hexadecyltrimethoxysilane were used for surface modification to obtain surface-modified magnetic particles of polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 290).

[0089] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0090] Comparative Example 5 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 4.68 g of dodecyltrimethoxysilane and 4.68 g of hexadecyltrimethoxysilane were used for surface modification to obtain magnetic particles with surface modified polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 25,000).

[0091] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0092] Comparative Example 6 A magnetorheological fluid was prepared according to the method of Example 1, except that in step (3), 4.68 g of dodecyltributoxysilane (C 12 H 25 -Si-(OC4H9)3) and 4.68 g hexadecyltributoxysilane (C 16 H 33 -Si-(OC4H9)3) was surface modified to obtain magnetic particles with surface modified polydodecylsiloxane and polyhexadecylsiloxane (weight average molecular weight of 5200).

[0093] The weight percentage of each component of the magnetorheological fluid in this comparative example is the same as that in Example 1.

[0094] Test Case Referring to the standard method JB / T 12512-2015, the magnetorheological fluids of the embodiments and comparative examples were subjected to sedimentation rate tests and magnetorheological property tests. The test results are listed in Table 1.

[0095] The sedimentation rate test method is: place the magnetorheological fluid in a 25mL measuring cylinder, seal it and let it stand at 25℃, observe the height of the upper clear liquid at the same time every day, and the sedimentation rate is the ratio of the height of the supernatant to the total height (25mL). The test time is 30 days.

[0096] The magnetorheological performance test method is: testing the zero-field viscosity of the magnetorheological fluid and the shear yield stress value under a 0.8T magnetic field in a rheometer according to a set program.

[0097] Table 1

[0098] As can be seen from Table 1, the magnetorheological fluid prepared in the example shows good sedimentation stability at a lower viscosity level, and also has a higher shear yield stress under a magnetic field.

[0099] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0100] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0101] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A magnetorheological fluid, characterized in that: The magnetorheological fluid contains magnetic particles with modified polysiloxane surfaces, wherein the polysiloxane is obtained by polycondensation of at least one silane with a general formula of X-Si-(OR)3, wherein X is selected from a substituted or unsubstituted alkyl group with 10 to 16 carbon atoms, and R is selected from a substituted or unsubstituted alkyl group with 1 to 3 carbon atoms, and the weight average molecular weight of the polysiloxane is 500 to 20,000.

2. The magnetorheological fluid according to claim 1, wherein: In the silane, the substituents in X and R are each independently selected from methoxy, ethoxy, halogen, hydroxyl, amino, thiol, carboxyl, amide, and nitrile; Alternatively, in the silane, X is selected from a linear alkyl group having 10 to 16 carbon atoms, and R is selected from a methyl group, an ethyl group, and a n-propyl group.

3. The magnetorheological fluid according to claim 1 or 2, wherein: The polysiloxane includes a first polysiloxane and a second polysiloxane, wherein the first polysiloxane is obtained by polycondensation of a first silane of a general formula X1-Si-(OR)3, and the second polysiloxane is obtained by polycondensation of a second silane of a general formula X2-Si-(OR)3, wherein X1 and X2 are each independently selected from a substituted or unsubstituted alkyl group having 10 to 16 carbon atoms, and the number of carbon atoms of X1 is less than the number of carbon atoms of X2.

4. The magnetorheological fluid according to claim 3, wherein: In the first silane, X1 is selected from a straight-chain alkyl group having 10 to 12 carbon atoms, and in the second silane, X2 is selected from a straight-chain alkyl group having 14 to 16 carbon atoms.

5. The magnetorheological fluid according to claim 1, wherein: The magnetorheological fluid further contains a base fluid and an additive. Based on the total weight of the magnetorheological fluid, the content of the magnetic particles is 70-85% by weight, the content of the base fluid is 12-22% by weight, and the content of the additive is 2-9% by weight.

6. The magnetorheological fluid according to claim 5, wherein: The base fluid includes one or more of mineral oil, synthetic hydrocarbon oil, ester oil, silicone oil, natural oil and fluorine oil.

7. The magnetorheological fluid according to claim 5, wherein: The additives include a thixotropic agent, an anti-wear agent and an antioxidant. Based on the total weight of the magnetorheological fluid, the content of the thixotropic agent is 1-4 weight %, the content of the anti-wear agent is 0.5-2 weight %, and the content of the antioxidant is 0.5-2 weight %.

8. The magnetorheological fluid according to claim 7, wherein: The thixotropic agent includes one or more of nano-silicon dioxide, diatomaceous earth, organic bentonite, polyolefin wax, polyfatty acid amide wax, hydrogenated castor oil, polyamide wax and polyvinyl chloride; and / or, The anti-wear agent comprises one or more of graphite, molybdenum disulfide, organic molybdenum compounds, sulfur-phosphorus compounds, chlorophosphorus compounds, chlorosulfur compounds, organic phosphides and organic metal salts; and / or, The antioxidant includes one or more of an organic phosphorus compound, an organic molybdenum compound, a zinc dialkyl dithiophosphate, a zinc alkyl thiocarbamate, a phenolic compound and a complex antioxidant.

9. The magnetorheological fluid according to claim 1, wherein: The magnetorheological fluid has a 30-day sedimentation rate of less than 20%, a zero-field viscosity of less than 500 mPa·s, and a shear yield stress of more than 70 kPa at a magnetic field strength of 0.8 T.

10. A method for preparing a magnetorheological fluid according to any one of claims 1 to 9, characterized in that: The method includes: obtaining an acidic solution containing alcohol and water; The mixture of magnetic particles, at least one silane of the general formula X-Si-(OR)3 and the acidic solution is subjected to hydrolysis and dehydration condensation reaction to obtain a reacted material; wherein X is selected from a substituted or unsubstituted alkyl group having 10 to 16 carbon atoms, R is selected from a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, the weight average molecular weight of the polysiloxane is 500 to 20,000, and the weight ratio of the magnetic particles to the silane is 100:(3 to 10); Washing and drying the reacted material to obtain polysiloxane surface-modified magnetic particles; The magnetorheological fluid is prepared by using the polysiloxane surface-modified magnetic particles.

11. The method according to claim 10, wherein: The acidic solution further contains glacial acetic acid; and / or the pH value of the acidic solution is 3-5.

12. The method according to claim 10, wherein: The weight ratio of the water to the alcohol is 1:(0.2-2); and / or, The weight ratio of the magnetic particles to the acidic solution is 1:(0.5-3).

13. The method according to claim 10, wherein: The hydrolysis conditions include: temperature of 20-30° C., stirring speed of 500-1000 rpm, and time of 1-5 h; and / or, The dehydration condensation conditions include: temperature of 50-90° C., stirring speed of 500-1000 rpm, and time of 0.1-5 h; and / or, The drying conditions include: a temperature of 70-90° C. and a time of 8-20 hours.

14. The method according to claim 10, wherein: The method further comprises: ball milling a mixture of the polysiloxane surface-modified magnetic particles, the base fluid and the additive to obtain the magnetorheological fluid; Optionally, the ball milling conditions include: a rotation speed of 300-500 rpm and a time of 4-12 h.

15. Use of the magnetorheological fluid according to any one of claims 1 to 9 in a vehicle shock absorption system.

Citation Information

Cited By

  • Magnetorheological fluid, and preparation method therefor and use thereof

    WO2026113646A1